2005
DOI: 10.1007/s11089-005-5581-3
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Restraints: Alternatives to Restraints on an Inpatient Psychiatric Service?Utilizing Safe and Effective Methods to Evaluate and Treat the Violent Patient

Abstract: This paper describes the violence safety program instituted at Elmhurst Hospital Center in Queens, New York City in 2001, which significantly reduced the use of restraints and seclusion department wide, while providing a safe and therapeutic environment for patient recovery. The hospital service and program instituted is described, followed by restraint and seclusion data since 1998, and the program's results through 2003. Concurrent data in areas that could be affected by a reduction in restraint and seclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 8 publications
0
88
0
1
Order By: Relevance
“…For example, one study of a hospital in New York reported reductions in restraint/seclusion despite the 'one hour rule' (reassessment of a patients within one hour of initiating restraint or seclusion) and other regulations being in place for some time before a range of interventions were introduced (26). In another study, JCAHO standards were introduced in the middle of the study period, but did not appreciably contribute to the already reduced levels of restraint/seclusion episodes (27).…”
Section: Changes In State or Local Policymentioning
confidence: 99%
See 3 more Smart Citations
“…For example, one study of a hospital in New York reported reductions in restraint/seclusion despite the 'one hour rule' (reassessment of a patients within one hour of initiating restraint or seclusion) and other regulations being in place for some time before a range of interventions were introduced (26). In another study, JCAHO standards were introduced in the middle of the study period, but did not appreciably contribute to the already reduced levels of restraint/seclusion episodes (27).…”
Section: Changes In State or Local Policymentioning
confidence: 99%
“…The training content tended to focus on aspects of crisis intervention or non-violent interventions as alternative to restraint, such as de-escalation techniques (26)(27)(28)(31)(32)(33)(34)(35)(36)(37)(38) or aspects of violence awareness or risk assessment (24,36,37,39). One study reported that requirements for staff training had been formalised but provided no details (20).…”
Section: Staff Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical psychiatry, the balance between care, security, and abuse is challenging. Thus, there is an overall intention to limit the use of coercion to an absolute minimum, and there is national [1] as well as international [2][3][4] focus on how this can be achieved. Knowledge on factors influencing the use of coercion is mandatory to optimize the situation.…”
Section: Introductionmentioning
confidence: 99%